P864 Frailty is associated with fatigue in older patients with Inflammatory Bowel Disease. (30th January 2023) - Fons, A; Asscher, V; van der Meulen-de Jong, A; Stuyt, R; Baven-Pronk, M; van der Marel, S; Jacobs, R; Mooijaart, S; Kalisvaart, K; Maljaars, J
Abstract: Background: Fatigue is a common and debilitating symptom experienced by patients with inflammatory bowel disease (IBD). Studies focusing on fatigue in IBD were conducted in a relatively young population. However, little is known about the prevalence and factors associated with fatigue in the older population with IBD and how it relates to frailty. Methods: The aim of this study was to determine the prevalence of fatigue and to identify factors associated with fatigue in older patients with IBD. Data were used from a prospective, multicenter cohort study, that included both older patients with IBD (aged > 65 years) and younger patients with IBD (aged < 65 years). Patients aged < 65 years served as a control group to compare the fatigue prevalence found in older patients. A geriatric assessment (including the Geriatric 8 (G8) questionnaire) was performed to measure frailty at baseline in older subjects. Fatigue was evaluated using one item from the Short Inflammatory Bowel Disease Questionnaire (SIBDQ). Univariable and multivariable regression analysis were performed to assess factors associated with fatigue in older patients with IBD. Active disease was defined as the presence of clinical or biochemical disease activity. Results: Fatigue prevalence in 405 older patients with IBD varied between 45.8% (71/155) in patients with active disease to 23.6% (59/250) in patients with disease in remission. In younger patients, fatigue prevalence varied between 59.5% (47/79) in active disease to 55.3% (42/76) in disease in remission. Multivariable analysis showed a significant association between fatigue and depression (Odds ratio (OR) 2.98, 95% confidence interval (CI) 1.23-7.17), sleeping disturbances (OR 4.25, 95% CI 2.40-7.54), use of immunomodulators (OR 2.24, 95% CI 1.15-4.38), and an abnormal frailty screening (G8) (OR 2.02, 95% CI 1.14-3.57). Frailty measured by geriatric assessment (OR 2.47, 95% CI 1.49-4.12) was also independently associated with fatigue. No association was found between fatigue and disease activity in multivariate analysis. Conclusion: Fatigue has a lower prevalence in older patients with IBD compared to younger patients with IBD, but the prevalence increased sharply when active disease is present. Fatigue in older patients is associated with depression, sleeping disturbances and use of immunomodulators. Moreover, both risk of frailty in frailty screening and frailty measured in a geriatric assessment associate with fatigue in older patients with IBD.